Shelter upgrading for the urban poor : evaluation of Third World experience - Skinner, R. J. (Reinhard J.), 1950-; Taylor, John L.; Wegelin, Emiel A. (Manila, Philippines : Island Pub. House, 1987)
Includes bibliographies and index.